Adverse Effects of Oral Cannabidiol: An Updated Systematic Review of Randomized Controlled Trials (2020-2022) - José Diogo R. Souza; Julia Cozar Pacheco; Giordano Novak Rossi; Bruno O. de-Paulo; Antonio W. Zuardi; Francisco S. Guimarães; Jaime E. C. Hallak; José Alexandre Crippa; Rafael G. Dos Santos (MDPI AG, 2022)
(1) Background: With the massive demand for the use and commercialization of medicinal cannabidiol (CBD) products, new randomized clinical trials (RCTs) are being published worldwide, with a constant need for safety and efficacy evaluation. (2) Methods: We performed an update on a systematic review published in 2020 that focused on analyzing the serious adverse effects (SAEs) of CBD in RCTs and its possible association with drug interactions. We also updated the report of the most prevalent CBD adverse effects (AEs). We systematically searched EMBASE, MEDLINE/PubMed, and Web of Science without language restriction for RCTs that reported adverse effects after repeated oral CBD administration for at least one week in healthy volunteers or clinical samples published from January 2019 to May 2022. The included studies were assessed for methodological quality by the Quality Assessment of Controlled Intervention Studies tool. The present review is registered on PROSPERO, number CRD42022334399. (3) Results: Twelve studies involving 745 randomized subjects analyzed were included (range 1.1-56.8 y). A total of 454 participants used CBD in the trials. The most common AEs of CBD were mild or moderate and included gastrointestinal symptoms (59.5%), somnolence (16.7%), loss of appetite (16.5%), and hypertransaminasemia (ALT/AST) (12.8%). Serious adverse effects include mainly hypertransaminasemia with serum levels elevations greater than three times the upper limit of the normal (6.4%), seizures (1.3%), and rash (1.1%). All SAEs reported in the studies were observed on CBD as an add-on therapy to anticonvulsant medications, including clobazam and valproate. (4) Conclusion: Recent RCTs involving oral CBD administration for at least a week suggest that CBD has a good safety and tolerability profile, confirming previous data. However, it can potentially interact with other drugs and its use should be monitored, especially at the beginning of treatment.